กระบวนการใช้ทุนทางสังคมเพื่อความมั่นคงทางอาหารของชุมชนประมงพื้นบ้าน: Process of Social Capital Utilization for Enhancing Food Security Among Local Fishing Communities - สิงห์ชัย อนุรักษ์; ทรัยพ์นาวิน ศุภณัฐ (Journal of Humanities and Social Sciences (HUSOKKU), 2026)
This research article aimed to investigate the process through which social capital was mobilized to sustain food security within a small-scale fishing community. The study adopted a qualitative research methodology grounded in a phenomenological approach, with units of analysis situated at both household and community levels. Fieldwork was conducted in the Laem Phak Bia small-scale fishing community, Ban Laem District, Phetchaburi Province, from December 2024 and May 2025. The key informants were categorized into two groups. The first group consisted of 40 households engaged in small-scale fisheries, while the second group comprised 9 community leaders and 10 community elders, yielding a total of 59 key informants. Data were collected through in-depth interviews in conjunction with semi-structured interviews. The data were subsequently analyzed using content analysis and presented through analytical description. The findings demonstrated that the process of mobilizing social capital for food security within the small-scale fishing community could be conceptualized into three interrelated phases. The first phase involved the formation of social networks and collaborative linkages with relevant institutions and external agencies. The second phase centered on the cultivation of trust, social cohesion, and legitimacy in community leadership. The third phase involved the conversion and utilization of social capital to secure access to community resources, including food security, cultural capital, economic capital, and symbolic capital. The study further revealed that social capital functioned as a crucial social resource underpinning the community’s food security and collective capacity for adaptation. Moreover, the process of mobilizing social capital enabled its transformation into other forms of capital, particularly cultural, economic, and symbolic capital, which reinforced livelihood sustainability and strengthened the community’s resilience amid ongoing socio-economic and environmental transformations.